The criminal career: Estimates of the duration and frequency of crime commission - Rhodes, William (Journal of quantitative criminology, 1989)
This paper deals with measuring two dimensions of the criminal career: residual duration and frequency. It reports results from estimating the parameters of a model in which offenders have a probability of desisting from further participation in crime following a conviction and, if they persist, a rate of crime commission. The probability of desisting and the rate of commission are seen as varying with offenders' personal characteristics and criminal records. Moreover, this paper discusses the difficulty of estimating models in which failure to commit a new crime might be attributable either to termination of the criminal career or to a censored follow-up period. The paper reports both successful and unsuccessful estimation attempts and discusses complications when distinguishing empirically between duration and frequency.